2023
DOI: 10.3390/electronics12163535
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of ChatGPT on Fostering Concept Generation in Innovative Product Design

Stefano Filippi

Abstract: The growing demand for innovative and user-centric product design has led to a growing need for effective idea generation methods. In recent years, natural language processing (NLP) tools such as ChatGPT have emerged as a promising solution for supporting idea generation in various domains. This paper investigates a framework for studying the role of ChatGPT in facilitating the ideation process in product design. This investigation measures the impact of ChatGPT on the generation of innovative concepts compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The generative AI design tools capable of operating in the early Concept and Embodiment design stages are general purpose tools built upon natural language processing. The flexibility afforded by the text representation of designs allows the tools to operate across broad design principles with high abstraction and ambiguity (Filippi, 2023). This generality and therefore lack of specialised physics models prevents these tools from operating in the Detail design stage, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generative AI design tools capable of operating in the early Concept and Embodiment design stages are general purpose tools built upon natural language processing. The flexibility afforded by the text representation of designs allows the tools to operate across broad design principles with high abstraction and ambiguity (Filippi, 2023). This generality and therefore lack of specialised physics models prevents these tools from operating in the Detail design stage, however.…”
Section: Discussionmentioning
confidence: 99%
“…This process is illustrated in Figure 2. The 15 tools selected for review were: TRIZ (Gadd, 2011;Petrov, 2023), Functional Analysis (Little, Wood and McAdams, 1997), Brainstorming (Putman and Paulus, 2009), ChatGPT (Filippi, 2023), Morphological Analysis (Arciszewski, 2018), DALL-E (Bing, 2023;Brisco, Hay and Dhami, 2023), CATIA GDE (Dassault Systemes, 2020), Inspire (Lim and Wong, 2018), Ansys (Ansys, 2021), Abaqus (Johnsen, 2013), Sulis (Altair, 2023;Das et al, 2023), Siemens NX (Menninger, Berroth and Jacobs, 2022;Siemens, 2023a), AutoDesk Fusion 360 (AutoDesk, 2023), Simulink (MathWorks, 2023) and Amesim (Siemens, 2023b). The four italicised early-stage design tools in this list are not computational methods.…”
Section: Desktop Reviewmentioning
confidence: 99%
“…The paper via several machine design examples, reports hallucinating formulas, selecting the wrong procedures to solve problems, and wrong mathematical calculations. A framework is proposed to assess ChatGPT's impact on generating innovative concepts in product design (Filippi, 2023). The study found that ChatGPT increased the quantity of concepts generated, but concepts were less useful compared to classic design methods.…”
Section: Can Ai and Gpt Fill In The Gap?mentioning
confidence: 99%
“…Recent advancements in, and especially within the last year, artificial intelligence (AI) and natural language processing (NLP) have captured the attention of academia and industry due to the increase in the availability of free, easy-to-use tools such as ChatGPT and similar prompt-based generative AI tools. Multiple engineering disciplines have experimented with and adopted these tools, solving tasks such as calculations in mechanical engineering (Tiro, 2023), assessing engineering students (Qadir, 2023) as a means of fostering concept generation in product design (Filippi, 2023) and writing academic papers (Thunström, 2022). It has already started transforming the way engineers write code (Ahmad et al, 2023), and it has been used as a tool for optimising 3D printing processes (Badini et al, 2023) and to generate functional 3D models iteratively (Nelson et al, 2023).…”
Section: Introductionmentioning
confidence: 99%